BOOK REVIEWS (Heythrop journal, 1995)
Books reviewed in this article: Understanding the Word: Essays in Honour of Bernhard W. Anderson. Edited by James T. Butler, Edgar W. Conrad and Ben C. Ollenburger. A Word in Season: Essays in Honour of William McKane. Edited by James D. Martin and Philip R. Davies. The Prophet Amos: A Translation and Commentary. By J. Alberto Soggin. Her Price is Beyond Rubies: The Jewish Woman in Graeco-Roman Palestine. By Léonie J. Archer. JSOT Supplement Series 60. The Gospel of Luke (Sacra Pagina 3). By Luke Timothy Johnson. The Acts of the Apostles (Sacra Pagina 5). By Luke Timothy Johnson. Mark and Method: New Approaches in Biblical Studies. Edited by Janice Capel Anderson and Stephen D. Moore. Jesus the Exorcist: A Contribution to the Study of the Historical Jesus (Wissenschaftliche Untersuchungen zum Neuen Testament 2/54). By Graham H. Twelftree. The Death of the Messiah: A Commentary on the Passion Narratives in the Four Gospels. By Raymond E. Brown. Paul and rhe Popular Philosophers. By Abraham J. Malherbe. History of New Testament Research, Volume One: From Deism to Tubingen. By William Baird. Theological Ethics of the New Testament. By Eduard Lohse. Living a Christian Life: Vol. 2 of The Way of the Lord Jesus. By Germain Grisez. Moral Demands and Personal Obligations. By Josef Fuchs. Plurality and Chrisrian Ethics. By Ian Markham. The Nature of Moral Thinking. By Francis Snare. Ethics (Oxford Readers). Edited by Peter Singer. Goodness and Rightness in Thomas Aquinas's ‘Summa Theologiae’. By James F. Keenan. Divine Power: The Medieval Power Distinction up to its Adoption by Albert, Bonaventure and Aquinas. By Lawrence Moonan. Preserving the Creation: Environmental Theology and Ethics. Edited by Kevin W. Irwin and Edmund D. Pellegrino. Religion and the Making of Society. By Charles Davis. The Good Stewards: Practical Applications of the Papal Social Vision of Work. By Michael Naughton. Things Old and New: Catholic Social Teaching Revisited. Edited by Francis P. McHugh and Samuel Natale. The Church Faces the Modern World: ‘Rerum Novarum’ and its Impact. Edited by Paul Furlong and David Curtis. Catholic Social Thought and the New World Order: Building on One Hundred Years. Edited by Oliver F. Williams and John W. Houck. The Church and Morality: An Ecumenical and Catholic Approach. By Charles E. Curran. God, Truth and Reality: Essays in Honour of John Hick. Edited by Arvind Sharma. Christianity and Chinese Religions. By Hans Kiing and Julia Ching. The Catholic Church in Modern China: Perspectives. Edited by Edmond Tang and Jean-Paul Wiest. Education And Meaning: Philosophy in Practice. By Paddy Walsh. Detachment and Concern: Conversations in the Philosophy of Teaching and Teacher Education. By Margret Buchman and Robert Floden. Hollywood Censored: Morality Codes, Catholics and the Movies (Cambridge Studies in the History of Mass Communications). By Gregory D. Black. Monastic and Religious Orders in Britain, 1000–1300 (Cambridge Medieval Textbooks). By Janet Burton. The Early Reformation in Europe. Edited by Andrew Pettegree.